Evaluasi Drug Related Problems (DRPs) pada Pasien Penyakit Jantung di Poli Penyakit dalam RSU Royal Prima Marelan - Innaya Sabrina Sirait; Razoki Razoki; Nerly Juli Pranita Simanjuntak (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Heart disease is the leading cause of death in Indonesia. The use of complex drugs in the treatment of heart disease increases the risk of Drug Related Problems (DRPs), especially due to the many comorbidities and drug interactions. The purpose of this study was to determine the incidence of Drug Related Problems (DRPs) in heart disease patients at the internal medicine clinic of Royal Prima Marelan Hospital. This study is a retrospective descriptive study of 50 outpatients diagnosed with heart disease in the period January-June 2024. Data obtained from medical records and patient prescriptions were analyzed to identify the types of DRPs based on the PCNE classification. Drug interactions were the most prevalent type of DRP (95,7%), with severity levels classified as moderate (80,5%), minor (12,6%), and major (4,4%). The most frequent interactions occurred between clopidogrel and omeprazole (major). Most patients were male (60%) and aged between 40-55 years (54%).